Understanding sleep health challenges of defence shift workers to design a digital, sleep and circadian management tool - Prerna Varma; Lin Shen; Svetlana Postnova; Kylie King; Mark E. Howard; Eugene Aidman; Shantha W. M. Rajaratnam; Tracey L. Sletten (Scientific Reports)
Abstract Defence personnel need to be agile and responsive in their assessment of strategic and tactical tasks. Sleep and circadian disruptions, however, can compromise personnel’s readiness. Digital health technologies have the potential to provide sleep and circadian health management advice but need to be designed with active involvement from stakeholders and communities. This study explored challenges with shift work in a cohort of defence personnel to identify end-user expectations for a sleep health smartphone application. Eight shift working Air Traffic Control personnel from the Australian Defence Force participated in 60-70-minute semi-structured online interviews. Informal discussions were also held with various defence stakeholders to determine requirements for an app. Defence personnel reported disruptions to their sleep, family, and social life due to environmental and operational circumstances, such as shift work, mental load, and unplanned schedules. They were highly receptive to a digital intervention and emphasised need for personalised support. Gamification, availability of the app via the defence forces, and high data security were recognised as key enablers. These insights should serve as theoretical foundation for further development, co-design, and testing of digital health tools in other shift worker cohorts, and to better examine and address the impacts of operational demands on their health and performance.